"Have I argued with my family this week?": What questions do those with lived experience choose to monitor their bipolar disorder? - Gordon-Smith, K; Saunders, KEA; Savage, J; Craddock, N; Jones, I; Jones, L (Elsevier, 2020)
Background: Electronic self-report mood monitoring tools for individuals with bipolar disorder (BD) are rapidly emerging and predominately employ predefined symptom-based questions. Allowing individuals to additionally choose what they monitor in relation to their BD offers the unique opportunity to capture and gain a deeper insight into patient priorities in this context.